2018
DOI: 10.1002/cctc.201800188
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Alloyed PtCu Nanocubic Frames with Three‐Dimensional Molecular Accessible Surfaces for Boosting Oxygen Reduction and Glycerol Oxidation Reactions

Abstract: Three‐dimensional (3D) hollow nanoframes with high surface‐to‐volume ratio and abundant accessible active sites are a type of promising catalysts, albeit with the challenging synthesis by a one‐step solvothermal method. In this research, uniform bimetallic PtCu alloyed hollow cubic nanoframes (HCNFs) were synthesized with high yield by a simple, template‐free, one‐step co‐reduction approach, where cetyltrimethylammonium chloride (CTAC), Cl−/O2, ethanolamine, and oleylamine served as the structure director, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Pt 0.25 Cu electrocatalyst still exhibits good activity ( E o 0.97 V vs. RHE) vs. Pt/C ( E o 0.95 V vs. RHE). After ADTs, Pt 0.25 Cu electrocatalyst exhibits high activity compared to Pt/C, due to the electron interaction effect between Pt−Cu and high SSA . Table S2 compares the catalytic activity of Pt 0.25 Cu electrocatalyst with the published in the literature.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Pt 0.25 Cu electrocatalyst still exhibits good activity ( E o 0.97 V vs. RHE) vs. Pt/C ( E o 0.95 V vs. RHE). After ADTs, Pt 0.25 Cu electrocatalyst exhibits high activity compared to Pt/C, due to the electron interaction effect between Pt−Cu and high SSA . Table S2 compares the catalytic activity of Pt 0.25 Cu electrocatalyst with the published in the literature.…”
Section: Resultsmentioning
confidence: 77%
“…In this study, Pt−Cu NPs are rich in Cu, leading to enhanced catalytic activity. The alloying Pt with 3d transition metals can change the electronic structure of Pt, thus prompting the O 2 reduction . The presence of Cu may enhance the OH ˗ generation, and thus improving CO tolerance .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, uniform PtCu alloy hollow cubic NFs were synthesized by Wang et al, and these 3D nanoarchitectures show the larger specific as well as mass activities and improved durability toward ORR in comparison with the Pt nanocubes, commercial Pt/C as well as Pt black catalyst under alkaline solution (Wang et al, 2018a).…”
Section: Applications In Fuel Cellsmentioning
confidence: 99%
“…[5,6] However, monometallic Au suffers from deactivation due to nanoparticle sintering or to the formation of carbonyl compounds irreversibly adsorbed on the active sites of the catalysts. [7][8][9][10] Many papers reported the synergistic effect of bimetallic structures in different catalytic reactions, such as PtCu alloys, [11,12] or PtPd alloys [13] compared to monometallic Pt. As well as Y. Wang et al [14] reported a synergistic effect in a bimetallic structure of ZnO and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%